The Sense and Non-sense of Revolt: not only about Julia Kristeva - Baranova, Jūratė (Religija ir kultūra, 2011)
Jean-Paul Sartre presupposed that we are condemned to liberty. One is open to free choice. There is no possibility not to choose. In this article when formulating hypotheses of investigation several rhetorical questions are asked: how to find the criterion for justification that the choice of revolt is really free choice, but not the psychological determinism caused by the pressure of unconsciousness. The other relevant question the answer for is researched in this article is such: if one is choosing freedom as the starting value point for one’s views, is it possible to him / her to stay consequently devoted to freedom in practical life? In this article we are investigating the ambiguity of the concept of freedom choosing the example of Sartre as philosopher, literary man, and practical rebel. The main issue of the article is such: there in no possibility to reconcile the practical Sartrean attitude towards revolt and his theoretical conception of freedom. His practical standpoint demonstrates the ambiguity and split of value points. The conception of revolt suggested by Albert Camus as individual’s resistance against the absurdity of existence demonstrates the possibility of much more consequent standpoint in theory and practical life.
Keywords: liberty; revolt; individual resistance; Kristeva; Sartre; Camus